Media Sosial, Demokrasi dan Problem Etika - Agus Sudibyo (Institut Media Digital Emtek, 2018)
There is a certain dualism of the social media in the context of institutionalizing the values of democracy and public sphere. On the one hand, the social media seems to be able to overcome the paradox of mass communication by making each individual the subject of its own by him or herself. In the social media there is no hierarchical dischotomy between the elite and the common people which is usually the case in mass communication. In the social media , each individual is the producer –and in the same time –the publisher and information discourse. Yet, on the other hand , this deliberativedemocratic social media carries its negative side causing a rather serious impact is becoming a communication sphere with an anti-communication character; a communication based on prejudice, a priori and indifference towards the feelings of others. How can it be called communication when its reality it has become the means to curse, hate and propogate sarcasm towards others? The social media is presenting some very serious ethical problems in to our public sphere and the promotion of democracy. The social media is in hand is worth it by the sphere of promotion. Sphere Is